Quality of Life among Patients with Cardiovascular Diseases at Birat Medical College Teaching Hospital (Journal of Nobel Medical College, 2023)
Background: Modern healthcare delivery needs to take care of the quality of life of patients. The burden of cardiovascular disease is increasing each year affecting the quality of life. So, we aimed to examine the quality of life of patients with cardiovascular diseases (CVD) at Birat Medical College Teaching Hospital.Materials and Methods: A hospital based cross sectional study was conducted among cardiovascular disease patients at Birat Medical College Teaching Hospital from 2023 Jan 27 to 2023 March 27.  Ethical clearance was taken from the institutional review committee. The collected data was entered in Microsoft Excel 2019 and analyzed by IBM SPSS statistics 2025.Results: Among 256 patients, the majority 67(26.2%) were in the age of 61-70 years and male 156(60.9%). Majority 91(35.5%) had coronary artery diseases. The quality of life domains ranging from least  to most  affected were  bodily pain (81.04±26.02), mental health (76.4±15.18), social functioning (68.1±24.2), role limitation due to emotional problems (67.9±43.56), physical functioning (59.02± 28.9), vitality (53.67±15.45), general perception of health (50.19±15.7) and role limitation due to physical health (46.39± 44).   Conclusion: Patients with cardiovascular disease had their quality of life affected based on their physical health, general perception of health, energy and vitality, physical functioning, role limitation due to emotional problems, social functioning, mental health and bodily pain